Lansoprazole-induced osteoporosis via the IP3R- and SOCE-mediated calcium signaling pathways - Ziping Cheng; Yangjie Liu; Mengyuan Ma; Shiyu Sun; Zengqing Ma; Yu Wang; Liyuan Yu; Xuping Qian; Luning Sun; Xuehui Zhang; Yun Liu; Yongqing Wang (BMC, 2022)
Abstract Background Many clinical studies have shown a correlation between proton pump inhibitors (PPIs) and osteoporosis or fractures. The purpose of this study was to establish a murine model of chronic oral PPI administration to verify whether PPIs caused bone metabolic impairment and investigate the relevant molecular mechanism underlying the effects of PPIs on MC3T3-E1 murine osteoblasts. Methods A lansoprazole-induced bone loss model was used to investigate the damaging effects of PPIs. In vivo, immunohistochemistry, Hematoxylin-Eosin (HE) staining, micro-CT analysis, and blood biochemical analyses were used to evaluate the effect of lansoprazole on bone injury in mice. In vitro, the effects of lansoprazole and related signaling pathways in MC3T3-E1 cells were investigated by CCK-8 assays, EdU assays, flow cytometry, laser confocal microscopy, patch clamping, reverse transcription-quantitative polymerase chain reaction and Western blotting. Results After 6 months of lansoprazole gavage in ICR mice, the micro-CT results showed that compared with that in the vehicle group, the bone mineral density (BMD) in the high-dose group was significantly decreased (P < 0.05), and the bone microarchitecture gradually degraded. Biochemical analysis of bone serum showed that blood calcium and phosphorus were both decreased (P < 0.01). We found that long-term administration of lansoprazole impaired skeletal function in mice. In vitro, we found that lansoprazole (LPZ) could cause calcium overload in MC3T3-E1 cells leading to apoptosis, and 2-APB, an inhibitor of IP3R calcium release channel and SOCE pathway, effectively blocked increase in calcium caused by LPZ, thus protecting cell viability. Conclusions Longterm administration of LPZ induced osteoporotic symptoms in mice, and LPZ triggered calcium increases in osteoblasts in a concentration-dependent manner. Intracellular calcium ([Ca2+]i) persisted at a high concentration, thereby causing endoplasmic reticulum stress (ERS) and inducing osteoblast apoptosis.